Business networks, social capital and the productivity of creative industries in Indonesia - Fikri Zul Fahmi (European Regional Science Association (ERSA), 2016)
This study examines the role of social and professional networks in the productivity of creative firms in Indonesia. In so doing, mixed methods are employed, including multilevel modelling as well as qualitative analysis, which is also performed to elaborate further on the process in which networking affects productivity. The Indonesian government promotes traditional businesses as creative industries, but they actually have different characteristics and networks. Therefore, in this paper creative and traditional cultural industries are differentiated. The results of multilevel analysis show that social capital is associated differently with the productivity of both types of industries. Creative industries appear to benefit from friendship, which facilitates their networking and creative processes. Meanwhile, friendship is negatively associated with the productivity of traditional cultural industries. This conclusion is affirmed by the qualitative analysis, which demonstrates that the relationship between friendship and productivity is rather complex. On the one hand, friendship helps firms find and develop their networked consumers. On the other hand, such strong ties between firm owners often lead to social events and gathering and thus, eliminate competition. Further to this, enhancing the productivity of these industries is better done not by forming associations which may only strengthen their bonding ties. Rather, providing common spaces that can facilitate cross-fertilization of ideas in a serendipitous and inclusive climate would be more effective.
Keywords: D22; R11; L25; L26; 330; creative industries; business networks; social capital; Indonesia